Pengaruh Budaya Kerja Kekeluargaan terhadap Turnover Intention melalui Komitmen Afektif - FIRMANTO, TITO (Jurnal Ilmu Manajemen (JIM), 2013)
The work culture of kinship as good communications between the employees and employee family need. However, there is a turnover intention on employee to happen turnover its year. This is alleged lack off affective commitment on employee themselves. This study aims to examine the direct effect of work-family culture to turnover intention and the indirect effect of work-family culture to turnover intention with affective commitment as a mediator. Sampling method using purposive sampling with employee PT. Boma Bisma Indra (Persero) Surabaya as a population, so the number of sample obtained amounted to 66 employee. The method of data analysis using multilevel linear regression assisted with SPSS 11.5 software. The result of the analysis in this study showed that work-family culture negative and not significant on the turnover intention of employees directly. While indirect relationship between work-family culture to turnover intention through affective commitment there is a negative relationship but significant. Keyword: work-family culture, affective commitment, turnover intention.